E-Marketing and Halal Product Assurance - Razali, Ramadhan; Maulina, Isra; Sufrizal (Jurisprudensi: Jurnal Ilmu Syariah, Perundang-Undangan dan Ekonomi Islam, 2022)
The purpose of this study is to analyze the implementation of UU-JPH in Aceh Province and the extent to which halal product labeling is produced through e-marketing. The type of this research is qualitative research with literature review data collection method. In this study, the authors analyze the implementation of the UU-JPH in Aceh Province and the development of selling halal products through e-marketing. In this study, researchers also discussed the development of halal labeling. The conclusion of this research is that the implementation of UU-JPH in Aceh Province has not been maximized. In addition, in the e-marketing strategy, halal labels are essential to increase people's buying interest